Black Internationalist Feminism : Women Writers of the Black Left, 1945-1995 - Higashida, Cheryl (Book collections on Project MUSE., 2011)
'Black Internationalist Feminism' examines how African American women writers affiliated themselves with the post-World War II Black Communist Left and developed a distinct strand of feminism.